Update on the Financing of the IMF's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2008)
This paper provides a semi-annual review of the status of financing for Poverty Reduction and Growth Facility-Exogenous Shocks Facility (PRGF-ESF) lending, subsidization of emergency assistance to PRGF-eligible countries, and Heavily Indebted Poor Countries (HIPC) and Multilateral Debt Relief Initiative (MDRI) debt relief. The last review was completed by the IMF Executive Board on April 21, 2008.